Characterisation, Modelling, Finite element analysis, and optimisation of hyperelastic materials for Non-Pneumatic Wheels - Bhartu, Saahil (University of the Witwatersrand, Johannesburg, 2024)
This abstract concludes the exploration of hyperelasticity within the context of mechanical engineering. Through this section, we have delved into the substantial elastic deformations characteristic of hyperelastic materials, their capacity for energy conservation during deformation, and their inherently non-linear behaviour. The calibration of non-linear material models has been informed by a rigorously designed experimental regimen, where preferred methodologies and necessary precautions were identified to ensure the integrity of the data obtained. Theoretical foundations for the development of constitutive models have been established, with a discussion of prevalent models frequently employed in engineering applications. Practical modelling applications introduced have provided a tangible context for the utilization of hyperelastic material models. While our focus was predominantly on nearly or fully incompressible materials, foundational concepts for compressible behaviour were also addressed, setting the stage for further investigative pursuits. Polyurethane (PU) materials exemplify hyperelastic behaviour. Through computational simulation, we assessed the deformation in a structured wheel to be 4.6mm, utilizing a 9;5 and 2 parameter Mooney-Rivlin model for the PU material. Experimental testing was conducted measuring deformation to be 4.1mm From the results, the deformation patterns, stress distributions, and contact pressures were analysed, indicating the wheel’s ability to endure a contact pressure of 7.36MPa, deformation of 4.6mm, Von-Mises stress of 3.9MPa. This investigation not only corroborates the distinctive properties of hyperelastic materials but also illustrates how analysis results can inform and optimize design iterations. It demonstrates the practical applications of hyperelastic material models in design engineering, providing a comprehensive understanding that is indispensable for the modelling and analysis of hyperelastic components.
A research report submitted in fulfillment of the requirements for the Master of Science in Engineering, In the Faculty of Engineering and the Built Environment , School of Mechanical, Industrial and Aeronautical Engineering, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Hyperelastic Materials; Non-Pneumatic Wheels (NPT); Finite Element Analysis (FEA); Polyurethane; Modelling and Simulation; Mechanical Engineering; Stress-Strain Behaviour; Material Characterization; Mechanical Properties; Polymer Engineering; Design Optimization; Manufacturing Processes; SDG-12: Responsible consumption and production